Comparative analysis of soccer clubs with formation teams from different contexts - SANTOS, Artur Jorge; GONÇALVES, Carlos Eduardo (Brazilian journal of physical education and sport, 2015)
The sport clubs are influenced during their existence and function by the environment where they're implemented, but can influence the individuals that are involved in the club, through organizational culture. Due to the different club context specificities it urges a data necessity about the clubs function, which will allow the implementation of intervention programs. This study pretends to analyse and compare three clubs from different contexts. For data, we selected by convenience three clubs, one professional and two amateurs, one of rural area and other from urban area. The AAC-OAF presents differences from the amateur clubs, being more oriented to sport performance/spectacularization. The amateur clubs are based on volunteering, depend more from local policies and authorities and reveal more difficulties in recruit volunteers, mainly, for management. The acceptance of manager's positions in the amateur clubs is due to the fear of extinction the club services. The financial stability of the UCE contributes for changes on organization culture and function. All the clubs present deficiencies in the evaluation process of the programs implementation for youth developmental, recurring more to the competition results.